Dynamic Response Analysis of Tilting Pad Journal Bearing Considering Fluid-Structure Interaction - Q. Li (Isfahan University of Technology, 2021)
The transient hydrodynamic lubrication model of tilting pad journal bearings (TPJBs) was established by the computational fluid dynamics (CFD) method and the self-developed dynamic grid program. The fluid-structure interaction between the flow field and the rotor motion, the pads rotations was realized. The feasibility of the model is proved by comparing with the experimental data. The dynamic response of TPJBs under the various unbalance, the loading modes and the rotating speeds was studied. The dynamic response of TPJBs is further analyzed through a research of the relationships among the shaft whirl orbits, transient force acting on the shaft, rotation angles of the pads and transient oil film force of the pads. With the increase of unbalance, the whirl orbits expand and whirl orbits centers rise continuously. The whirl orbits and orbit center attitude angles of TPJBs are smaller than those of fixed-pad journal bearings. Compare with the load between pads, the whirl orbits are smaller and whirl orbits centers drop slightly under the load on pads. With the increase of rotating speed, the whirl orbits expand nonlinearly, whirl orbit center rises nonlinearly. The transient force acting on the shaft, the rotation angles of the pads and the transient oil film force of the pads change periodically, and the period and frequency of these changes are the same as that of the shaft rotation. The maximum force acting on the shaft appear before the maximum shaft center position (the vertexes of the whirl orbit).